(3GdebGdI GdfGUQjI aj GdJOGHjQ GdUMjIs - (3CSYO Hf EdjGS Hf GdeWQGf, GdOeTbj,J (B587 (3g` s ((3eGdc GHf CHj GdaJM Hf CHj GdfLe GdeJWHH s)
(3ChdgG (B:s
(3hHYO (B: (3adeG QCjJ eG QRb Gddg ehdGfG Gdedc GdfGUQ UdGM GdOfjG hGdOjf CHG GdeXaQ jhSa Hf CjhH Hf TGPi , GYR Gddg CfVGQg s
(3BNQgG (B:s
(3hEf hUd GdCeQ HJYOjd Pdc hHSWg hTQMg , aYd Pdc MSH Gdhab Gdehdhi s
(3CdagG HQSe Gdedc GdfGUQ UdGM GdOjf GdCjhHis
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3JHUQI GdYfhGf (B:s
(3LeY s
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdWHs